The Effectiveness Of Learning Motivation In Improving Communicative Competence Among Learners Of Arabic At The Faculty Of Sharia Sultan Sharif Ali Islamic University/ فعالية الدوافع التعلميّة في تعزيز الكفاية الاتصالية لدى دارسي اللغة العربية في كلية الشريعة بجامعة السلطان الشريف علي الإسلامية - Achmad Yani; Siti Sara Binti Haji Ahmad; Rafidah Binti Abdullah; Siti Shalihah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the effectiveness of learning motivation among students of the Faculty of Sharia at Sultan Sharif Ali Islamic University in Brunei Darussalam, in the context of communicative Arabic language learning. The study employed a quantitative descriptive-evaluative approach to measure motivational indicators and their behavioral, cognitive, and emotional manifestations, using a closed-ended questionnaire built on established theoretical foundations such as self-determination theory (Deci Ryan, 1985), the expectancy-value model (Eccles Wigfield, 2002), and the three-part engagement model (Fredricks et al., 2004). The sample size was 22 students, representing 63% of the total study population. They were selected using the partial enrollment method, as all were actively engaged in learning the course during the 2024 academic year. The data underwent rigorous statistical analysis using relative equality and relative weighting on a five-point Likert scale, with the results interpreted based on a modern theoretical framework. The results indicate that the majority of students are highly motivated to learn communicative Arabic (77.3%), and there is a strong correlation between this motivation and positive academic behaviors, such as class participation and assignment completion. The results also reveal a gap in emotional engagement (neutrality 54.5%), which necessitates a review of content delivery methods and educational incentives. The study concludes with key recommendations, particularly: redesigning the curriculum to consider the affective dimension, enabling interactive technologies, developing assessment methods, and training teachers in emotional and linguistic motivational strategies. The study also calls for longitudinal and qualitative studies, the development of explanatory models linking motivation and learning outcomes, and opening avenues for regional cooperation in the field of teaching Arabic as a second language. This study contributes to enriching the literature on motivation in language learning and offers an applied model that can be used in developing Arabic language teaching policies in multilingual Islamic environments, while drawing attention to the integration of psychological and pedagogical dimensions in the educational process.